Fatores que influenciam o desempenho de uma rede de cooperação horizontal : um estudo de caso das redes de Cascavel - PR - Ferraz, Luciana Maria Santos (2015)
A technological revolution transformed society and the global economic scenario in the late twentieth century. This new context, which is marked by uncertainty and constant and highly competitive changes, imposes new challenges to managers of SME (Small or Medium Enterprise) seeking strategic advantages to compete with large companies. Alternatively, there are the horizontal cooperation networks, a new form of organization and relationship between companies. It is an associative model, where companies in the same economic sector and with common goals, unite in pursuit of greater competitiveness and better results.In order to provide a better understanding of the subject, this paper aims to analyze, from the manager perspective, the factors that influence the performance of horizontal cooperation networks from Cascavel (PR-BR). To do so, we use a methodology study of multiple exploratory and qualitative approach cases. Interviews were conducted with managers of two networks for data collection. They were intentionally selected, depending on the accessibility and development stage. Seven managers of each of the selected networks were also interviewed along with a Sebrae’s consultant and an Apras’s consultant. The research was completed with a documentary analysis. After data analyzes, it was observed that the formation of networks generates benefits that are not always perceived by entrepreneurs due to their individual goals. It was also noted a lack of commitment of the members and a very strong culture of competition. Those are factors that have a direct impact in the performance of horizontal cooperation networks of Cascavel.